A Combined Algorithm for Data Cleaning of Wind Power Scatter Diagram Considering Actual Engineering Characteristics. (October 2020) - Wu, JiaHui; Shao, ZhenGuo; Yang, ShaoHua
Abstract: There exist a lot of outliers in the wind power scatter diagram, which due to communication failure, equipment abnormality, artificial power limitation, and other reasons in the actual operation of wind turbines. These outliers have an adverse effect on performance and status evaluations for wind turbines seriously. Firstly, the reasonable power offset ranges are calculated using the affine algorithm, which considers actual engineering characteristics, e.g., forecast error and topographic difference. Besides, the quartering algorithm is applied for clearing the scattered outliers. Furthermore, the affine-quartile combined algorithm is presented to realize advantageous complementarities and attain accurate data of the wind power scatter diagram. Finally, Case studies show that the proposed affine-quartile algorithm, with consideration of actual engineering characteristics, can improve the coverage and accuracy of outlier detection.